Aromatic plant-derived essential oil: An alternative larvicide for mosquito control - Pitasawat B. (2014)
Five aromatic plants, Carum carvi (caraway), Apium graveolens (celery), Foeniculum vulgare (fennel), Zanthoxylum limonella (mullilam) and Curcuma zedoaria (zedoary) were selected for investigating larvicidal potential against mosquito vectors. Two laboratory-reared mosquito species, Anopheles dirus, the major malaria vector in Thailand, and Aedes aegypti, the main vector of dengue and dengue hemorrhagic fever in urban areas, were used. All of the volatile oils exerted significant larvicidal activity against the two mosquito species after 24-h exposure. Essential oil from mullilam was the most effective against the larvae of A. aegypti, while A. dirus larvae showed the highest susceptibility to zedoary oil. © 2007 Elsevier B.V. All rights reserved.